Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s42466-021-00124-1
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Endoscopic Swallowing Evaluation for Tracheostomy Decannulation in Critically Ill Neurologic Patients – a prospective evaluation

Abstract: Background Removal of a tracheostomy tube in critically ill neurologic patients is a critical issue during intensive care treatment, particularly due to severe dysphagia and insufficient airway protection. The “Standardized Endoscopic Evaluation for Tracheostomy Decannulation in Critically Ill Neurologic Patients” (SESETD) is an objective measure of readiness for decannulation. This protocol includes the stepwise evaluation of secretion management, spontaneous swallowing, and laryngeal sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Similarly, though there are numerous complex algorithms to assess swallowing function prior to decannulation, the overall yield of such procedures may not justify their routine use in the clinical practice, particularly in developing nations. 14,15 As reiterated by the results of the present study, a simple transnasal flexible laryngoscopy seems to be sufficient to confirm an excellent swallowing function, with preserved laryngeal sensation and cough reflex, even in neurologically-ill patients. 6 However, our decannulation protocol is meant to be used only in patients who exhibit good swallowing function clinically (those accepting oral feeds well), and the method used is not meant to rate or assess the severity of aspiration or to provide corresponding prognostication of decannulation in patients with swallowing issues.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly, though there are numerous complex algorithms to assess swallowing function prior to decannulation, the overall yield of such procedures may not justify their routine use in the clinical practice, particularly in developing nations. 14,15 As reiterated by the results of the present study, a simple transnasal flexible laryngoscopy seems to be sufficient to confirm an excellent swallowing function, with preserved laryngeal sensation and cough reflex, even in neurologically-ill patients. 6 However, our decannulation protocol is meant to be used only in patients who exhibit good swallowing function clinically (those accepting oral feeds well), and the method used is not meant to rate or assess the severity of aspiration or to provide corresponding prognostication of decannulation in patients with swallowing issues.…”
Section: Discussionsupporting
confidence: 57%
“…These results are comparable with those the other methods described earlier, but our protocol is likely to be more cost-effective and feasible. [11][12][13][14][15][16] Around 4.5% of our patients had failed decannulation attempts, despite having been deemed fit for decannulation. The rate of failure, defined as the need to reinsert an artificial airway within a short while of being decannulated after successfully clearing a decannulation protocol, in the present study is similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 86%
“… 7 , 8 Several studies have employed observation of hypopharyngeal secretion retention as an essential screening step to exclude the patients without sufficient airway protection from decannulation in neurological Intensive Care Unit. 9 , 10 But the performance of hypopharyngeal secretion retention in diagnosis of readiness for tracheostomy removal has not been fully tested. Additionally, previous studies have reported more severe secretion retention in patients with a tracheostomy tube than in those without.…”
mentioning
confidence: 99%
“…Fiberoptic endoscopy has been reliably applied in assessment of readiness for decannulation in the sABI population. 9 , 10 , 13 It has been shown to be an objective and sensitive tool to allow the direct observation of secretions in the pharynx, and to evaluate swallowing function in patients with dysphagia. 14 Food/liquid aspiration and decreased laryngeal sensitivity detected by fiberoptic endoscopy are closely linked to compromised airway protection, a potential cause of prolonged tracheostomy or decannulation failure in patients with sABI; however, current studies have not discussed them as potential decannulation-outcome predictors.…”
mentioning
confidence: 99%
“…The two studies in question, a single-centre pilot study [ 4 ] and a multicentre trial [ 5 ], applied PES in tracheotomised stroke patients who had been weaned from mechanical ventilation but could not be decannulated because of severe dysphagia, a rather common situation in neurocritical care. Both studies used a well-established FEES-based protocol [ 6 , 7 , 8 ] to assess airway safety, a key and fundamental aspect of swallowing function, before and after intervention, i.e., PES or sham. This protocol consists of a stepwise evaluation of the following three items: Assessment of secretion: Does the patient present with a massive pooling of saliva or a silent penetration/aspiration of saliva?…”
mentioning
confidence: 99%